Research on the insurance underwriting model based on catastrophic risk - Zhong, Runyu; Li, Kaixin (Transactions on Economics, Business and Management Research, 2024)
The frequent occurrence of extreme weather events has led to significant property damage, and at the same time, the amount of natural disaster claims received by insurance companies has also increased dramatically. In order to more accurately assess insurance companies’ underwriting capacity and coverage of catastrophe risks, since catastrophe risks in Los Angeles and Guangzhou are more frequent and more representative, this paper takes these two places as examples and establishes catastrophe risk assessment index and catastrophe risk severity scale based on the time series method. Next, We comprehensively consider the time value of money, and based on the insurer’s surplus model, we aim to assist insurance companies in underwriting judgment and risk sharing decisions such as reinsurance, so as to provide a reasonable measurement standard for insurance companies.